Pharmacoepidemiological analysis of the effect of lipid-lowering therapy on cardiovascular mortality in the regions of the Russian Federation - I. S. Krysanov; V. S. Krysanova; V. Yu. Ermakova (Izdatelstvo OKI, 2022)
Objectives. Cardiovascular diseases (CVD) are one of the leading causes of death worldwide, including Russia. According to the data obtained from the ESSE-RF study, the most common risk factor for the development of CVD is high level of cholesterol. At the same time, among drugs that lower cholesterol levels, statins are the most studied. The main aim of the study was to conduct a retrospective pharmacoepidemiological study to assess the effect of hypolipidemic therapy on overall and cardiovascular mortality in the regions of the Russian Federation. Methods. At the first stage, the indicators of population, cardiovascular and overall mortality in 2012-2018 were analyzed for 84 subjects of the Russian Federation. The time period of the analysis is determined by the timing of the implementation of the Federal project "Combating Cardiovascular Diseases". Next, we analyzed the frequency of prescribing lipid-lowering therapy in high doses in 84 regions of the Russian Federation in 2014- 2018, according to IMS Health for 2 market segments (preferential and hospital). The number of patients receiving high-dose statins (HDS) (atorvastatin 40 and 80 mg, rosuvastatin 20 and 40 mg) was calculated based on sales volumes in natural terms. Results. Based on the analysis of cardiovascular mortality, all 84 regions of the Russian Federation were divided into 3 groups: high, medium and moderate mortality. In the high-mortality group, HDS consumption per patient averaged 4.45 patients per 100,000 population, in the moderate-mortality group, 19.39 patients, and in the moderate-mortality group, 21.51 patients. Conclusions. The results of the study showed that there is a relationship between the frequency of HDS use and cardiovascular mortality in the regions of the Russian Federation. These results may indicate the effectiveness of lipid-lowering therapy in real practice.